Systematics and palaeobiogeography of the Sub-Saharan Neoperla Needham stoneflies (Plecoptera, Perlidae) - Kirkaldy, Benjamin Phuleng (Rhodes University, 2026)
Neoperla is a widespread and diverse genus of Plecoptera (stoneflies), with 378 species recognized from Asia, America, and Africa. For most of the last 70 years, the Afrotropical Neoperla were treated as a single, widespread and heterogeneous species, Neoperla spio Newman. This gordian knot persisted until 2023, when 82 valid species were recognized across the Afrotropical region. As a result of this taxonomic uncertainty, remarkably little is known about the diversity, ecology and biogeographical history of Neoperla in Africa. In this thesis, I used newly collected specimens, museum collections, and published literature to address some of these gaps. Ten novel species of Neoperla were identified and described from Central and Southern Africa based on morphological and molecular evidence. A further five putative species were described, but are not recognized as species due to the unavailability of adult material. The taxonomy of Neoperla nymphs, which currently cannot be identified morphologically, was reviewed, and six species were described based on colouration patterns. A time-calibrated phylogeny of Neoperla was used to investigate the mechanisms behind the disjunct distribution of Neoperla, and its dispersal into Africa. The results of this analysis did not support any previous hypotheses, and a novel hypothesis that Neoperla spread into Africa and America via the North Atlantic land bridge during the Paleogene was presented. In the Afrotropical region, I propose that Neoperla radiated and dispersed alongside the evolution of drainage systems and rivers on the continent. To select calibration points for this time-calibrated phylogeny, the taxonomy of >100 fossil stoneflies was reviewed. I suggested the reclassification of almost 60% of these species, and proposed a novel assemblage of ten fossil calibration points that can be used for future phylogenetic and palaeobiogeographic analyses of Plecoptera. Finally, the diversity and ecology of the South African Neoperla species was reviewed, and the distribution, habitat, and river biotope preferences of nine South African species were summarized. A key for the identification of South African Neoperla nymphs was presented to facilitate further research on the genus.
Keywords: Biology--Classification (http://id.loc.gov/authorities/subjects/sh85014205); Paleoentomology (http://id.loc.gov/authorities/subjects/sh95005625); Species diversity (http://id.loc.gov/authorities/subjects/sh87005571); Phylogeny (http://id.loc.gov/authorities/subjects/sh85101498); Afrotropical realm (https://www.wikidata.org/wiki/Q388614); Neoperla spio (https://www.wikidata.org/wiki/Q6380782)